Evaluating urban agriculture program effectiveness using CIPP model: a review - Yusuf, Munifah Siti Amira; Man, Norsida; Mohamed Haris, Nur Bahiah; Ismail, Ismi Arif; Maruf, Amar (EDP Sciences, 2021)
The art of planting, preparing, and distributing food around urban areas is known as urban agriculture, farming, or gardening. Individuals and organizations generally work in urban agriculture for general purposes: 1) enhancing their own health and economic circumstances; 2) improving their communities’ access to nutritious food; 3) enhancing their community wellbeing; and 4) developing a community and ecosystem. The Urban Agriculture Program (UAP) has been set up by the Department of Agriculture (DOA) Malaysia since 2014 to facilitate and transfer information regarding urban farming practices to the community. However, the program was less effective and had a low success rate due to the local community's minimal participation, slow development, and sustainability of the agriculture community gardens. This article primarily examines the UAP implementation based on the four components of the CIPP Evaluation Model: Context, Input, Process, and Product. The UAP is a sustainable development tool that can provide food or related services within or on the edges of urban areas. Malaysia addresses food security by providing urban dwellers with adequate nutritious, safe, acceptable, and cost-effective food. Therefore, the study is relevant as achieving food security and nutrition that has been set in the urban agriculture program outcome by 2025.